Using pore-solid fractal dimension to estimate residual LNAPLs saturation in sandy aquifers: A column experiment - Lin Sun; Shuai-wei Wang; Cai-juan Guo; Chan Shi; Wei-chao Su (Journal of Groundwater Science and Engineering, 2022)
: The“tailing” effect caused by residual non-aqueous phase liquids (NAPLs) in porous aquifers is one of the frontiers in pollution hydrogeology research. Based on the current knowledge that the residual NAPLs is mainly controlled by the pore structure of soil, this study established a method for evaluating the residual saturation of NAPLs by investigating the fractal dimension of porous media. In this study, the soil column experiments of residual light NAPLs (LNAPLs) in sandy aquifer with different ratios of sands and soil were carried out, and the correlation between the fractal dimension of the medium, the residual of LNAPLs and the soil structure parameters are statistically analyzed, and its formation mechanism and main control factors are discussed. The results show that: Under our experimental condition: (1) the fractal dimension of the medium has a positive correlation with the residual saturation of NAPLs generally, and the optimal fitting function can be described by a quadratic model: SR=192.02D2−890.73D+1040.8; (2) the dominant formation mechanism is: Smaller pores in the medium is related to larger fractal dimension, which leads to higher residual saturation of NAPLs; stronger heterogeneity of the medium is related to larger fractal dimension, which also leads to higher residual saturation of NAPLs; (3) the micro capillary pores characterized by fine sand are the main controlling factors of the formation mechanism. It is concluded that both the theory and the method of using fractal dimension of the medium to evaluate the residual saturation of NAPLs are feasible. This study provides a new perspective for the research of “tailing” effect of NAPLs in porous media aquifer.